Habitat, space use and feeding ecology of the African buffalo - (:unkn) unknown (My University, 2023)
African buffalo herd size varies across their distribution range from as few as 5–10 in the rainforests of West and Central Africa to as many as 2000 individuals in the floodplains of eastern and southern Africa. The home range size of African buffalo also varies greatly, with those of savanna buffalo herds generally ranging between 50 and 350 km2. The larger home ranges are generally observed in areas where resources are spatially segregated, and where herds are forced to undertake seasonal movements. In contrast, forest buffalo exhibit smaller home ranges (<10 km2) due to a less pronounced seasonality of the environment, and a more homogeneous spatial arrangement of resources. African buffalo are ruminants, essentially feeding on grass and roughage. This species is capable of subsisting on pastures too coarse and too tall for most other herbivores. The African buffalo occupies an important niche, opening up habitats that are preferred by short-grass grazers. Although the African buffalo primarily is a grazer, savanna buffalo can partially switch their diet to browse when grasses become tall and lignified. The ability of the African buffalo to cope with contrasting environmental conditions throughout most sub-Saharan ecosystems, by modulating a large array of biological traits, highlights a high degree of behavioural plasticity.
Keywords: African Research